Listening to the future: spotify´s dominance through podcasts and emerging markets - Forte, Dinis da Silva (2022)
This Equity Research report conducted a valuation on Spotify, the leading company in the audio streaming sector. Being market leader, the company is expected to continue its current growth path, amplified by the opportunities to expand its premium and ad-supported segments in emerging markets, and the increased monetization of its advertising segment through podcasts. It is issued a “Buy” recommendation, with an expected price of €300,2per share in the end of 2022, translating in a 52% total return for shareholders.